High-fidelity QND readout and measurement back-action in a tantalum-based high-coherence fluxonium qubit - Bothara, Gaurav; Das, Srijita; Salunkhe, Kishor V.; Chand, Madhavi; Deshmukh, Jay; Patankar, Meghan P.; Vijay, R. (APL quantum, 2025)
Implementing a precise measurement of the quantum state of a qubit is critical for building a practical quantum processor, as it plays an important role in state initialization and quantum error correction. While the transmon qubit has been the most commonly used design in small- to medium-scale processors, the fluxonium qubit is emerging as a strong alternative with the potential for high-fidelity gate operation as a result of the high anharmonicity and high coherence achievable due to its unique design. Here, we explore the measurement characteristics of a tantalum-based high-coherence fluxonium qubit and demonstrate single-shot measurement fidelity (assignment fidelity) of 96.2% ± 0.5% and 97.8% ± 0.4% without and with the use of a Josephson parametric amplifier, respectively. We study the back-action of the measurement photons on the qubit and measure a QND fidelity of 99.0% ± 0.3%. We find that the measurement fidelity and the QND nature are limited by state-mixing errors, and our results suggest that a careful study of measurement-induced transitions in the fluxonium is needed to further optimize the readout performance.